"Audacity, audacity, still more audacity": Tim Buck, the Party, and the People, 1932-1939 - Manley, John (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2002)
Abstract In 1932, when Communist Party of Canada (CPC) general secretary Tim Buck, six other CPC leaders and one unfortunate rank-and-filer began lengthy sentences in Kingston penitentiary, the Party seemed to have reached its nadir. In fact, martyrdom proved to be a springboard for sustained political revival and was a particular boon to Buck, helping him consolidate a stirring performance in the dock at the Party trial a few months earlier. Until then, he had been considered something of a mediocrity, his status dependent almost entirely upon Moscow's grace and favour. During his three years in Kingston prison, the underground Party successfully reinvented him as the "dauntless leader of the Canadian working class": shortly after his release in November 1934, his five month-long coast-to-coast tour attracted (by the RCMP's almost certainly conservative estimate) a total audience of over 100,000. Buck proceeded to dominate the Party for the remainder of the decade — the Popular Front years — a period fondly recalled in his posthumous memoirs. Buck presented the Popular Front strategy as his — as much as "Moscow's" — invention and quietly attributed the Party's rise in fortunes (membership almost tripled) in large part to his bold and independent political leadership. The Popular Front was certainly good news for Buck, but whether it was good news for "Tim Buck's Party" is more open to question. This paper questions Buck's self-evaluation and suggests that the exposure of the cynical character of the Popular Front project in 1939 "may have planted the seeds of [the] Party's long postwar decline."